PROGRESSIVE METHODS OF SURGICAL TREATMENT OF INTRACEREBRAL BRAIN TUMORS - Khusanov Zafar Toshmurodovich (Web of Journals Publishing, 2024)
Brain tumors account for 1.8–2.3% of the structure of oncological diseases. The detection rate of primary breast tumors is 10.9–14.0 per 100 thousand population. Metastatic tumors of the brain are currently detected 5 times more often than primary tumors, and therefore metastatic tumor lesions of the brain are the most common among all tumor diseases of the central nervous system. In 50–60% of patients with brain tumors, involvement of functionally significant and vital brain structures in the pathological process is observed [1–3, 15, 17].